In this chapter, we provide RD Sharma Class 7 ex 7.2 Solutions Chapter 7 Algebraic Expressions for English medium students, Which will very helpful for every student in their exams. Students can download the latest RD Sharma Class 7 ex 7.2 Solutions Chapter 7 Algebraic Expressions Maths pdf, Now you will get step by step solution to each question.

Maths pdf, Now you will get step by step solution to each question.

Textbook | NCERT |

Class | Class 7 |

Subject | Maths |

Chapter | Chapter 7 |

Chapter Name | Algebraic Expressions |

Exercise | Ex 7.2 |

**RD Sharma Solutions for Class 7 Chapter 7 Decimals** **Ex 7.2 Download PDF**

**Chapter 7: Algebraic Expressions Exercise – 7.2**

**Question: 1**

Add the following:

(i) 3x and 7x

(ii) -5xy and 9xy

**Solution:**

We have

(i) 3x + 7x = (3 + 7) x = 10x

(ii) -5xy + 9xy = (-5 + 9)xy = 4xy

**Question: 2**

Simplify each of the following:

(i) 7x^{3}y +9yx^{3}

(ii) 12a^{2}b + 3ba^{2}

**Solution:**

Simplifying the given expressions, we have

(i) 7x^{3}y + 9yx^{3} = (7 + 9)x^{3}y = 16x^{3}y

(ii) 12a^{2}b + 3ba^{2 }= (12 + 3)a^{2}b =15a^{2}b

**Question: 3**

Add the following:

(i) 7abc, -5abc, 9abc, -8abc

(ii) 2x^{2}y, – 4x^{2}y, 6x^{2}y, -5x^{2}y

**Solution:**

Adding the given terms, we have

(i) 7abc + (-5abc) + (9abc) + (-8abc)

= 7abc – 5abc + 9abc – 8abc

= (7 – 5 + 9 – 8)abc

= (16 – 13)abc

= 3abc

(ii) 2x^{2}y +(-4x^{2}y) + (6x^{2}y) + (-5x^{2}y)

= 2x^{2}y – 4x^{2}y + 6x^{2}y – 5x2y

= (2- 4 + 6 – 5) x 2y

= (8 – 9) x 2y

= -x^{2}y

**Question: 4**

Add the following expressions:

(i) x^{3} -2x^{2}y + 3xy^{2}– y^{3}, 2x^{3}– 5xy^{2} + 3x^{2}y – 4y^{3}

(ii) a^{4} – 2a^{3}b + 3ab^{3} + 4a^{2}b^{2 }+ 3b^{4}, – 2a^{4} – 5ab^{3} + 7a^{3}b – 6a^{2}b^{2 }+ b^{4}

**Solution:**

Adding the given expressions, we have

(i) x^{3} -2x^{2}y + 3xy^{2}– y^{3}, 2x^{3}– 5xy^{2} + 3x^{2}y – 4y^{3}

Collecting positive and negative like terms together, we get

x^{3} +2x^{3 }– 2x^{2}y + 3x^{2}y + 3xy^{2} – 5xy^{2} – y^{3}– 4y^{3}

= 3x^{3} + x^{2}y – 2xy^{2 }– 5y^{3}

(ii) a^{4} – 2a^{3}b + 3ab^{3} + 4a^{2}b^{2 }+ 3b^{4}, – 2a^{4} – 5ab^{3} + 7a^{3}b – 6a^{2}b^{2 }+ b^{4}

a^{4} – 2a^{3}b + 3ab^{3} + 4a^{2}b^{2} + 3b^{4} – 2a^{4} – 5ab^{3 }+ 7a^{3}b – 6a^{2}b^{2} + b^{4}

Collecting positive and negative like terms together, we get

a^{4} – 2a^{4}– 2a^{3}b + 7a^{3}b + 3ab^{3} – 5ab^{3} + 4a^{2}b^{2} – 6a^{2}b^{2 }+ 3b^{4} + b^{4}

= – a^{4 }+ 5a^{3}b – 2ab^{3} – 2a^{2}b^{2 }+ 4b^{4}

**Question: 5**

Add the following expressions:

(i) 8a – 6ab + 5b, –6a – ab – 8b and –4a + 2ab + 3b

(ii) 5x^{3} + 7 + 6x – 5x^{2}, 2x^{2} – 8 – 9x, 4x – 2x^{2} + 3 x 3, 3 x 3 – 9x – x^{2} and x – x^{2} – x^{3} – 4

**Solution:**

(i) Required expression = (8a – 6ab + 5b) + (–6a – ab – 8b) + (–4a + 2ab + 3b)

Collecting positive and negative like terms together, we get

8a – 6a – 4a – 6ab – ab + 2ab + 5b – 8b + 3b

= 8a – 10a – 7ab + 2ab + 8b – 8b

= –2a – 5ab

(ii) Required expression = (5 x 3 + 7+ 6x – 5x^{2}) + (2 x 2 – 8 – 9x) + (4x – 2x^{2} + 3 x 3) + (3 x 3 – 9x-x^{2}) + (x – x^{2} – x^{3} – 4)

Collecting positive and negative like terms together, we get

5x^{3} + 3x^{3} + 3x^{3} – x^{3} – 5x^{2} + 2x^{2 }– 2x^{2}– x^{2} – x^{2} + 6x – 9x + 4x – 9x + x + 7 – 8 – 4

= 10x^{3} – 7x^{2} – 7x – 5

**Question: 6**

Add the following:

(i) x – 3y – 2z

5x + 7y – 8z

3x – 2y + 5z

(ii) 4ab – 5bc + 7ca

–3ab + 2bc – 3ca

5ab – 3bc + 4ca

**Solution:**

(i) Required expression = (x – 3y – 2z) + (5x + 7y – 8z) + (3x – 2y + 5z)

Collecting positive and negative like terms together, we get

x + 5x + 3x – 3y + 7y – 2y – 2z – 8z + 5z

= 9x – 5y + 7y – 10z + 5z

= 9x + 2y – 5z

(ii) Required expression = (4ab – 5bc + 7ca) + (–3ab + 2bc – 3ca) + (5ab – 3bc + 4ca)

Collecting positive and negative like terms together, we get

4ab – 3ab + 5ab – 5bc + 2bc – 3bc + 7ca – 3ca + 4ca

= 9ab – 3ab – 8bc + 2bc + 11ca – 3ca

= 6ab – 6bc + 8ca

**Question: 7**

Add 2x^{2} – 3x + 1 to the sum of 3x^{2} – 2x and 3x + 7.

**Solution:**

Sum of 3x^{2} – 2x and 3x + 7

= (3x^{2} – 2x) + (3x +7)

=3x^{2} – 2x + 3x + 7

= (3x^{2} + x + 7)

Now, required expression = 2x^{2 }– 3x + 1+ (3x^{2 }+ x + 7)

= 2x^{2 }+ 3x^{2} – 3x + x + 1 + 7

= 5x^{2 }– 2x + 8

**Question: 8**

Add x^{2 }+ 2xy + y^{2} to the sum of x^{2} – 3y^{2}and 2x^{2 }– y^{2} + 9.

**Solution:**

**Question: 9**

Add a^{3}+ b^{3} – 3 to the sum of 2a^{3} – 3b^{3 }– 3ab + 7 and -a^{3} + b^{3} + 3ab – 9.

**Solution:**

**Question: 10**

Subtract:

(i) 7a^{2}b from 3a^{2}b

(ii) 4xy from -3xy

**Solution:**

(i) Required expression = 3a^{2}b -7a^{2}b

= (3 -7)a^{2}b

= – 4a^{2}b

(ii) Required expression = –3xy – 4xy

= –7xy

**Question: 11**

Subtract:

(i) – 4x from 3y

(ii) – 2x from – 5y

**Solution:**

(i) Required expression = (3y) – (–4x)

= 3y + 4x

(ii) Required expression = (-5y) – (–2x)

= –5y + 2x

**Question: 12**

Subtract:

(i) 6x^{3 }−7x^{2 }+ 5x − 3 from 4 − 5x + 6x^{2} − 8x^{3}

(ii) − x^{2 }−3z from 5x^{2 }– y + z + 7

(iii) x^{3} + 2x^{2}y + 6xy^{2} − y^{3} from y^{3}−3xy^{2}−4x^{2}y

**Solution:**

**Question: 13**

From

(i) p3 – 4 + 3p^{2}, take away 5p^{2} − 3p^{3} + p − 6

(ii) 7 + x − x^{2}, take away 9 + x + 3x^{2} + 7x^{3}

(iii) 1− 5y^{2}, take away y^{3} + 7y^{2} + y + 1

(iv) x^{3} − 5x^{2} + 3x + 1, take away 6x^{2} − 4x^{3} + 5 + 3x

**Solution:**

**Question: 14**

From the sum of 3x^{2} − 5x + 2 and − 5x^{2 }− 8x + 9 subtract 4x^{2} − 7x + 9.

**Solution:**

**Question: 15**

Subtract the sum of 13x – 4y + 7z and – 6z + 6x + 3y from the sum of 6x – 4y – 4z and 2x + 4y – 7.

**Solution:**

Sum of (13x – 4y + 7z) and (–6z + 6x + 3y)

= (13x – 4y + 7z) + (–6z + 6x + 3y)

= (13x – 4y + 7z – 6z + 6x + 3y)

= (13x + 6x – 4y + 3y + 7z – 6z)

= (19x – y + z)

Sum of (6x – 4y – 4z) and (2x + 4y – 7)

= (6x – 4y – 4z) + (2x + 4y – 7)

= (6x – 4y – 4z + 2x + 4y – 7)

= (6x + 2x – 4z – 7)

= (8x – 4z – 7)

Now, required expression = (8x – 4z – 7) – (19x – y + z)

= 8x – 4z – 7 – 19x + y – z

= 8x – 19x + y – 4z – z – 7

= –11x + y – 5z – 7

**Question: 16**

From the sum of x^{2 }+ 3y^{2} − 6xy, 2x^{2} − y^{2} + 8xy, y^{2} + 8 and x^{2} − 3xy subtract −3x^{2} + 4y^{2} – xy + x – y + 3.

**Solution:**

**Question: 17**

What should be added to xy – 3yz + 4zx to get 4xy – 3zx + 4yz + 7?

**Solution:**

The required expression can be got by subtracting xy – 3yz + 4zx from 4xy – 3zx + 4yz + 7.

Therefore, required expression = (4xy – 3zx + 4yz + 7) – (xy – 3yz + 4zx)

= 4xy – 3zx + 4yz + 7 – xy + 3yz – 4zx

= 4xy – xy – 3zx – 4zx + 4yz + 3yz + 7

= 3xy – 7zx + 7yz + 7

**Question: 18**

What should be subtracted from x^{2} – xy + y^{2} – x + y + 3 to obtain −x^{2 }+ 3y^{2 }− 4xy + 1?

**Solution:**

**Question: 19**

How much is x – 2y + 3z greater than 3x + 5y – 7?

**Solution:**

Required expression = (x – 2y + 3z) – (3x + 5y – 7)

= x – 2y + 3z – 3x – 5y + 7

Collecting positive and negative like terms together, we get

x – 3x – 2y + 5y + 3z + 7

= –2x – 7y + 3z + 7

**Question: 20**

How much is x^{2} − 2xy + 3y^{2 }less than 2x^{2} − 3y^{2} + xy?

**Solution:**

**Question: 21**

How much does a^{2 }− 3ab + 2b^{2 }exceed 2a^{2 }− 7ab + 9b^{2}?

**Solution:**

**Question: 22**

What must be added to 12x^{3 }− 4x^{2} + 3x − 7 to make the sum x^{3} + 2x^{2 }− 3x + 2?

**Solution:**

**Question: 23**

If P = 7x^{2} + 5xy − 9y^{2}, Q = 4y^{2} − 3x^{2} − 6xy and R = −4x^{2} + xy + 5y^{2}, show that P + Q + R = 0.

**Solution:**

**Question: 24**

If P = a^{2} − b^{2} + 2ab, Q = a^{2 }+ 4b^{2} − 6ab, R = b^{2} + b, S = a^{2 }− 4ab and T = −2a^{2} + b^{2} – ab + a. Find P + Q + R + S – T.

**Solution:**

**All Chapter RD Sharma Solutions For Class 7 Maths**

I think you got complete solutions for this chapter. If You have any queries regarding this chapter, please comment on the below section our subject teacher will answer you. We tried our best to give complete solutions so you got good marks in your exam.